La lectura crítica y su influencia en el rendimiento académico de los estudiantes del sexto año de educación básica de la escuela “Francisco Sandoval Pástor” de la parroquia El Triunfo, cantón La Maná durante el periodo lectivo 2012 –2013 - Chichande Molina, Galud Pensilvania (2014)
This investigation had as aim to determine the influence of critical reading in the academic performance of students from Francisco Sandoval Pastor school during the academic year 2012 - 2013, to gather the information, it was necessary to use the technique like a survey for teachers and students of the sixth year of Basic Education, through the methodology it was possible to determine the main cause of the low academic performance of the students, due to the lack of application of adequate techniques; this investigation contributes with a very important information about the critical reading and its influence in the academic performance....